PENGEMBANGAN BISNIS JASA PEMASARAN DIGITAL "DIGITALEAD" DENGAN BUSINESS MODEL CANVAS - Pitrang, Hafidari Tapak; Pahlevi, Reza Widhar (Journal Competency of Business, 2022)
This research aims to analyze the business development of digital marketing services using the Business Model Canvas. The Business Model Canvas provides a comprehensive framework to understand a business, including its Customer Segments, Value Proposition, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partners, and Cost Structure. The study utilizes the Business Model Canvas as a tool to analyze a case study of a digital marketing services company and identify its strengths and opportunities for growth. The findings suggest that a well-designed business model can lead to successful business development and growth in the digital marketing industry. The research concludes by highlighting the importance of using a systematic approach such as the Business Model Canvas for analyzing business development in digital marketing services. The conclusion is that the development of a digital marketing services business is strongly influenced by internal and external factors of the company. Therefore, companies must continuously monitor and improve these factors to increase business competitiveness